2021
DOI: 10.1109/tcc.2019.2894768
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Opacity in Cloud Computing Systems

Abstract: Federated cloud systems increase the reliability and reduce the cost of the computational support. The resulting combination of secure private clouds and less secure public clouds, together with the fact that resources need to be located within different clouds, strongly affects the information flow security of the entire system. In this paper, the clouds as well as entities of a federated cloud system are assigned security levels, and a probabilistic flow sensitive security model for a federated cloud system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…For the IEEE 30 transport and IEEE 118 transport, the location likelihood and normal identification dormancy of the RPCA-based proximal inclination finder are given (Zeng, 2021). As per reproduction information, the Proximal Inclination finder calculation based RPCA can recognize FDIA with a higher identification likelihood of over 95%.…”
Section: Discussionmentioning
confidence: 99%
“…For the IEEE 30 transport and IEEE 118 transport, the location likelihood and normal identification dormancy of the RPCA-based proximal inclination finder are given (Zeng, 2021). As per reproduction information, the Proximal Inclination finder calculation based RPCA can recognize FDIA with a higher identification likelihood of over 95%.…”
Section: Discussionmentioning
confidence: 99%
“…Opacity is an increasing concern in a cyber-physical system. Most of the estimation algorithms allow sharing of explicit state information with neighboring nodes, resulting in the disclosure of the state of the cyber-physical system [9,10]. (4) Privacy and Confidentiality: The security of data is an important aspect and challenge for SG.…”
Section: An Overview Of Smart Grid Security Challengesmentioning
confidence: 99%
“…In this study, they showed the formal model of risk propagation. In references 16‐18, it was shown how modeling with Petri nets can help to analyze the information flow security in cloud computing systems. These studies did not consider the threats and risks of the systems.…”
Section: Related Workmentioning
confidence: 99%